Performance profiles of professional female tennis players in grand slams - Cui, Y.; Gómez, M.-A.; Gonçalves, B.; Sampaio, J. (PLOS ONE, 2018)
The aim of the study was to (i) analyze the match performance of professional female tennis players in different Grand Slams; (ii) model the relationships between match performance variables and relative quality; and (iii) build typical performance profiles for those players in Grand Slams. Method: Data of a total of 1369 matches were collected within 2014-2017 four Grand Slams (Australian Open: n = 499; Roland Garros: n = 249; Wimbledon: n = 249 and US Open, n = 372). Correlations between 37 performance variables and relative quality (difference of expected rounds between two competing players of given ranking) were determined and automatically classified into two groups of magnitudes via two-step cluster analysis. Higher-correlated variables were used to build players` typical performance profiles via regression-based technique to give percentage evaluation scores (%ES), which means the percentage of matches where a performance variable value would be expected to be lower than the observed value considering the RQ of two competing players. Results: Players had more service winners, double faults, return winners and return unforced errors in the Australian Open and US Open, implying a "fast-fast" serve strategy, and higher dominance ratio and better serving performance in Wimbledon. While receiving players had better chances to break opponents` service game in Roland Garros. Distance covered became similar in all Grand Slams. All studied variables showed obvious correlation with RQ expect for those of physical performance. Conclusions: The findings (i) indicate that female game in Grand Slams remained to be a contest over baseline, although players had good efficiency at net; (ii) demonstrate the influence of relative quality on serve and return, break point, net point and efficiency performance; and (iii) evidence the usefulness of applying %ES to evaluate performance of individual player.